A systematic review of determinants of breast cancer risk among women with benign breast disease - Aileen Burke; Jessica O’Driscoll; Mustapha Abubakar; Kathleen E. Bennett; Emma Carmody; Fidelma Flanagan; Gretchen L. Gierach; Maeve Mullooly (npj Breast Cancer)
Abstract Benign breast disease (BBD) is associated with heterogeneous breast cancer risk. Identifying key breast cancer risk factors for this population may inform breast cancer prevention or early detection strategies. We systematically searched literature databases PubMed, Embase, Scopus, Web of Science, and the Cochrane Library to identify studies reporting associations of demographic, lifestyle, reproductive, and radiological factors with risk of breast cancer among women with biopsy-confirmed BBD. 67 studies met eligibility criteria. Variation was observed for study time period, exposure measurement, comparison groups, outcomes, and adjustment for confounders, precluding meta-analysis. The literature suggested positive risk associations for age at biopsy, family history, mammographic breast density, and time since biopsy, and no association for body mass index, alcohol, smoking, age at menarche, and use of hormonal contraceptives. More research is needed to understand risk factor associations among women with BBD, particularly studies that account for heterogeneity within BBD and breast cancer.